2020
DOI: 10.1680/jener.19.00076
|View full text |Cite
|
Sign up to set email alerts
|

Socio-technical transitions in UK electricity: part 2 – technologies and sustainability

Abstract: J G (2020) Socio-technical transitions in UK electricity: part 2-technologies and sustainability. Proceedings of the Institution of Civil Engineers-Energy, 173 (3). pp. 123-136.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Energy systems are undergoing disruptive change. In the UK, the number of decentralized energy operations is on the increase [15]. These changes are motivated in part by an increasing political drive in response to environmental policy priorities.…”
Section: Context and Motivationmentioning
confidence: 99%
“…Energy systems are undergoing disruptive change. In the UK, the number of decentralized energy operations is on the increase [15]. These changes are motivated in part by an increasing political drive in response to environmental policy priorities.…”
Section: Context and Motivationmentioning
confidence: 99%
“…The quite dramatic rise in the uptake of RETs over the past few decades are associated with a significant decline in their levelised costs. Higher penetrations of low-cost RETs will then lead to falls in GHG emissions from the UK power sector to near-zero by around 2030-2035(CCC, 2019a2019b;Foxon et al, 2020). Electrification in the steel sector implies a reliance on producing recycled steel from scrap in Electric Arc Furnaces (EAFs) (currently only around 30% of the sector output), the generation of electricity from low-CO2 sources [e.g., nuclear power and RETs (mainly solar photovoltaic arrays and wind turbines)], and the shutting down of Blast Furnace (BF)-coke oven production using mainly virgin ores (Griffin and Hammond, 2021).…”
mentioning
confidence: 99%
“…It opens with a topical briefing on the use of the rapid pyrolysis process to generate hydrogen (H 2 ) from natural gas (NG). Clarke and Abánades (2021) identify this as a potentially important component of a 'low-carbon' transition pathway (Foxon et al, 2020a(Foxon et al, , 2020b. This is typically referred to as 'blue hydrogen', because of the significant carbon dioxide content of NG (producing hydrogen at 40 gCO 2 e/kWh), in contrast to currently more expensive 'green' hydrogen processing by way of electrolysis that greatly reduces the generation of carbon dioxide emissions in order to underpin a net-zero economy (yielding hydrogen at 14 gCO 2 e/kWh).…”
mentioning
confidence: 99%
“…The application of environmental life-cycle assessment (LCA) to evaluate the impact of solar hot water (SHW) systems is reviewed by Wei et al (2021) to examine their impacts. They note that LCA (see also Foxon et al (2020b) for an outline of the methods and sources) can identify the environmental impacts over the full supply chain from 'cradle-to-grave' (or, more commonly, 'cradle-to-gate'). In the case of SHW systems, they found that such impacts mainly emanate from manufacturing and acquisition of raw materials, which depend on the type of system and their embedded materials.…”
mentioning
confidence: 99%